Decitabine for Relapsed Acute Lymphoblastic Leukemia after Allogeneic Hematopoietic Stem Cell Transplantation - 崔杰克;肖音;游泳;石威;李青;罗毅;蒋林;仲照东 (Current medical science, 2017)
Relapse after allogeneic hematopoietic stem cell transplantation（allo-HSCT） remains a main question on treatment failure. Current strategies for management that usually include salvage chemotherapy, donor lymphocytic infusion and second transplantation. Our study assessed the efficacy of decitabine（DAC） for treating patients with acute lymphoblastic leukemia（ALL） who relapsed after allogeneic hematopoietic stem cell transplantation（allo-HSCT）. We retrospectively analyzed the outcomes of 12 patients with relapsed ALL after allo-HSCT who received DAC therapy. Nine patients received DAC combined with chemotherapy and donor stem cell infusion, and 3 patients received single-agent DAC. Ten of the 12 patients achieved complete remission（CR）, 1 achieved a partial remission（PR）, and 1 had no response（NR） after treatment at the latest follow-up（LFU）, the median survival was 11.2 months（range, 3.8–34, 7 months）. The 1-and 2-year overall survival（OS） rates were 50%（6/12） and 25%（3/12）, respectively. Five patients were still alive; 4 had maintained CR and 1 was alive with disease. Patients with Philadelphia chromosome-positive ALL had higher survival rate than patients with Philadelphia chromosome-negative ALL（57.1% vs. 20%）. No aggravated flares of graft-versus-host disease（GVHD） were observed during DAC treatment. Therefore, DAC may be a promising therapeutic agent for ALL recurrence after allo-HSCT.